2010
DOI: 10.1128/aem.02520-09
|View full text |Cite
|
Sign up to set email alerts
|

Census of the Viral Metagenome within an Activated Sludge Microbial Assemblage

Abstract: The viral metagenome within an activated sludge microbial assemblage was sampled using culture-dependent and culture-independent methods and compared to the diversity of activated sludge bacterial taxa. A total of 70 unique cultured bacterial isolates, 24 cultured bacteriophages, 829 bacterial metagenomic clones of 16S rRNA genes, and 1,161 viral metagenomic clones were subjected to a phylogenetic analysis.Bacteriophages play an active role in the ecology of natural environments, influencing prokaryotic popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 18 publications
1
51
2
Order By: Relevance
“…A metagenomics analysis of reclaimed water (for nonpotable public uses) using pyrosequencing of viral particle-associated DNA indicated 98% prokaryotic versus 2% eukaryotic viral sequences, while the viral RNA population showed a more equally mixed distribution of viruses from a variety of inferred hosts more akin to that reported here (82). A metagenomics analysis of DNA viruses purified from activated sludge (a product of wastewater treatment) also showed a predominance (95%) of prokaryotic DNA viruses (76). A pyrosequencing analysis of the DNA viruses in the influent, activated sludge, effluent, and anaerobic digester of a wastewater treatment plant showed Ͼ90% of viral reads to be of likely bacterial origin (89).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A metagenomics analysis of reclaimed water (for nonpotable public uses) using pyrosequencing of viral particle-associated DNA indicated 98% prokaryotic versus 2% eukaryotic viral sequences, while the viral RNA population showed a more equally mixed distribution of viruses from a variety of inferred hosts more akin to that reported here (82). A metagenomics analysis of DNA viruses purified from activated sludge (a product of wastewater treatment) also showed a predominance (95%) of prokaryotic DNA viruses (76). A pyrosequencing analysis of the DNA viruses in the influent, activated sludge, effluent, and anaerobic digester of a wastewater treatment plant showed Ͼ90% of viral reads to be of likely bacterial origin (89).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that besides human viruses, untreated sewage also contains a wide diversity of other animal, plant, insect, and bacterial viruses (11,76,82,89). We performed a metagenomic deep-sequencing analysis of viral particles in sewage from four countries on three continents.…”
mentioning
confidence: 99%
“…Bacteriophages are ubiquitous and abundant components of microbial communities and have significant influence upon bacterial diversity, horizontal gene transfer, and genetic diversity in environmental habitats (43). By counting the number of reads mapped to each phage-related contig and normalizing by the total read count, it was possible to estimate the relative abundance of phages.…”
Section: Statistics Of Sequences Generated By 454 Pyrosequencingmentioning
confidence: 99%
“…Low-complexity sequence regions (simple sequence repeats) were identified and excluded from consideration during initial pair-wise comparison but were included during final alignment and consensus building. Assembled contigs longer than 10 kb were assigned to their taxonomic affiliations by BLASTN comparisons to the GenBank nonredundant nucleotide (nr/nt) database and selections of the top BLASTN hits for phylogenetic affiliation as described previously (43,44). Clustered regularly interspaced short palindromic repeats (CRISPR) elements were searched from assembled contigs longer than 10 kb by using the Web-based tool CRISPRFinder (18).…”
mentioning
confidence: 99%
“…2). It has previously been shown that environmental phages in wastewater, sludge and soil contain 16S rRNA genes of bacterial origin (Sander & Schmieger, 2001, Del Casale et al, 2011aParsley et al, 2010;Ghosh et al, 2008).…”
Section: H Perlevis and Seawater Phages Contain Bacterial Genesmentioning
confidence: 99%